India's Commercial Banks and Strategic Management Principles: Exploring the Impact of Privatisation on India's Public Sector Banks (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Financial institutions play a crucial role in fostering economic growth. Public sector banks(PSBs) in India have neglected the requirements of the economy and its stakeholders. Despite multiplepolicy modifications implemented in the past decade, the issue of underperformance in PSB hasendured. In contrast, private banks have experienced a notable surge in their market share and overallperformance. The present essay advocates for the privatisation of Public Sector Banks (PSBs). Due to itsexceptional performance and alignment with the PSBs' growth objectives, we recommend retaininggovernment control over the SBI in the interim period, while privatising the remaining banks. The initialpair of banks selected for privatisation ought to exhibit exceptional asset quality and elevated returns,thereby setting a benchmark for forthcoming privatisation endeavours. The efficacy of privatisation iscontingent upon the government's relinquishment of its position on the bank's board subsequent to theprivatisation process. The research proposes several alternative pathways to effectively transition theindustry towards private ownership. The statement cautions that the present circumstances will result ina persistent decrease in the market share of Public Sector Banks (PSBs), ultimately impeding India'seconomic advancement. Additionally, it will impose substantial costs on depositors, businesses,taxpayers, and the government, which is the primary owner of these banks.